ASPEK PERSUASIF DALAM BAHASA IKLAN PARTAI POLITIK - Dwi Budiyanto (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe persuasive aspects in the language of political party advertisements. This was a qualitative study using a semiotic analysis of television advertisements of political parties in the 2009 general election. The data were collecting through careful reading and taking notes. The data were analyzed by means of the inductive comparative technique, categorization, data display, and inference making. The findings are as follows. The persuasive aspects in the language of advertisements of political parties in the 2009 general election consist of two forms, i.e.: (a) presentation of message contents: informational, emotional, and motivational persuasions; and (b) presentation of message styles: hyperbole, imperative, metaphor-simile, acronymy, synecdoche, repetition, irony, and rhetorical question.